Role of cross-diagonal reinforcements in lieu of seismic confining stirrups in the performance enhancement of square RC columns carrying axial load subjected to close-range explosive loading - Anas, S. M.; Alam, Mehtab; Isleem, Haytham F.; Najm, Hadee Mohammed; Sabri Sabri, Mohanad Muayad (Frontiers in Materials, 2022)
Exposure of building infrastructures to accidental or intentional blasts is an extreme load condition that may cause irreparable damage leading to the collapse of buildings. Columns being principal elements are most important for the stability and safety of the buildings under accidental explosions and subversive blasts events, and therefore attract the attention of structural engineers and researchers. Some recent examples are the Beirut seaport explosion (August 2020), the explosion at an ammunition warehouse in Ryazan city of Russia (October 2020), the gas explosion in China’s Hubei province (June 2021), blast at a chemical factory on the outskirts of Bangkok (July 2021), and the explosion on a container ship docked at Dubai’s Jebel Ali port (July 2021). In the crises like ongoing conflict between Russia and Ukraine, the enhanced response of the principal components of a structure may save the life of the building users by limiting the severe damage to the structure. In this study, three experimentally tested 3000mm long normal strength concrete columns, 300mm x 300mm, provided with (i) conventional reinforcement, (ii) seismic reinforcements over top and bottom confining regions (600mm), and (iii) seismic reinforcement over confining and mid-height regions, carrying an axial working load of 950kN available in the literature are modeled in ABAQUS 2020 code and are subjected to 82kg TNT close-range explosive load at scaled distance 1.0m/kg1/3 using the software’s explicit module. In addition to this, one column with seismic reinforcement over its entire length has been considered and modeled. The Concrete Damage Plasticity model is implored for nonlinear elastic and inelastic behaviors, degradation of stiffness, and loading rate effect on concrete. Following the validation of the numerical models, the seismic reinforcements of the columns have been replaced by the cross-diagonal reinforcements between the conventional stirrups with the same axial load. Blast performance of the columns with the seismic reinforcements and with replaced diagonal reinforcements are critically examined and discussed. Results show that the application of cross-diagonal reinforcements as a replacement for the seismic reinforcements enhances the blast resistance of the RC column significantly by reducing the damage and displacement.